Conceptualising the politics of social protection expansion in low income countries: The intersection of transnational ideas and domestic politics. (6th April 2016) - Lavers, Tom; Hickey, Sam
Abstract : The growing literature on social protection in low income developing countries has tended to focus on definitional debates, policy design and impact evaluations, with relatively little consideration of the ways in which politics shape policy. This article argues that politics needs to be at the centre of efforts to understand social protection and outlines a new conceptual framework for investigating this, with a particular focus on explaining the variation in progress made by low income countries in adopting and implementing social protection. We propose that an adapted 'political settlements' framework that incorporates insights from the literatures on welfare state development – notably 'power constellations' theory, discursive institutionalism and global policy networks – can help frame political commitment to social protection as flowing from the interaction of domestic political economy and transnational ideas. Importantly, this approach situates social protection within a broader political and policy context, and highlights the influence of underlying power relations at multiple levels.